The Children Language Practice Among Mixed Marriage: Stories of Two Sundanese-Sulawesinese and Javanese-Balinese Families - Akbar, Rezky Arbima (Language Horizon: Journal of Language Studies, 2021)
This paper focuses on "the children language practice among mixed marriage families". How do they teach children's language practices in their daily life. Effects on their children. Will their child learn and master the language of the area where their parents come from. The last is in their child's identity. This study used qualitative method that conducted by the interview. There are two subjects used in this study that come from different tribes in Indonesia. The first subject came from a mixed marriage between Sunda-Sulawesi families who now live in Jombang, East Java and the second mixed marriage families between Java-Bali, where the family now lives in Surabaya, East Java. After finding a mixed marriage families that was properly used as the subject of this study, interviews were conducted by providing several questions. Interviews between mother and father of both subjects were used in this study. Based on the results of the interview, several different things were found and also the factors that made a difference between the two mixed marriage families such as every family of mixed marriages families have their own way of teaching children's language practices, the environments factors that influence children's language practice.